Pelaksanaan Inovasi Pembelajaran Kitab Kuning di Pondok Pesantren - Zulheddi, Zulheddi; Muammar, Muammar; Said, Salim (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The purpose of this study was to find out the implementation and learning of the yellow book which was carried out at Islamic boarding schools. This research is a qualitative research, researchers conduct research naturally to capture everything that happens in the field directly to be used as data. Data collection techniques using interviews, observation and documentation. The approach used is descriptive. The informants of this study were the head of the madrasah and teachers. Data analysis techniques using data reduction, data presentation and drawing conclusions by testing the validity of the data using credibility, transfer, dependability and suitability tests. The results of this study indicate that: The implementation of learning the yellow book at Islamic boarding schools is so that students have extensive religious knowledge and quality intellectuals so that they are able to practice it in everyday life and have noble character or piety morality (religious quality) in the students themselves. The process of innovation in the learning of the yellow book can be seen when the teacher enters the classroom, the teacher of the yellow book says greetings, in unison the students immediately stand up and then answer the teacher's greeting and the students sit after the teacher sits down and it has become a habit for the yellow book teaching teachers before reading the teachers' book. previously presented surah al-Fatihah to the Prophet and the author of the book, then the teacher started reading the yellow book with various kinds of material or different books according to the book to be taught. Keywords: Learning Innovation, Yellow Book